KONSENTRASI FOLIAR SPRAYING PUPUK BERTEKNOLOGI NANO DAN MEDIA TANAM PADA PERTUMBUHAN DAN HASIL TANAMAN ZUKINI (Cucurbita pepo L.) - Widiatmanta, Jeka; Wibowo, Agung Setya; Serdani, Army Dita; Puspitorini, Palupi; Qoyim, Zainul (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2023)
Zucchini (Cucurbita pepo L.) is a member of the Cucurbitaceae group that is of interest to the public because it has high economic value. However, there are obstacles to cultivation, one way to overcome them is by using nano technology fertilizer and planting media. The aim of this research was to find out the interaction between doses of nanote chnology compound fertilizer and planting media on the growth and yield of zucchini plants (Cucurbita pepo L.). The research method used was a Factorial Randomized Block Design with two factors. First factor: concentration of compound fertilizer with nano technology (P) which consists of 4 levels, namely: P0: control (without application of nano technology fertilizer) P1: concentration of nano fertilizer 5 ml/L P2: concentration of nano fertilizer 10 ml/L P3: concentration of fertilizer nano 15 ml/L Second factor: the composition of the planting medium which consists of 3 levels, namely: M1: Husk charcoal: cocopeat: vermicompost (1:1:1) M2: Husk charcoal: cocopeat: vermicompost (1:1:2) M3: Husk charcoal: cocopeat: vermicompost (1:1:3) Variables observed were plant height (cm), stem diameter (cm), flowering time (DAT), fruit diameter (cm), fruit weight (grams) and fruit length (cm ). From the research results it can be concluded that there is a real interaction in the treatment of nano fertilizer and planting media. The best combination was seen in the application of 10 ml/L nano fertilizer and husk charcoal planting media: cocopeat : vermicompost (1:1:3) (P2M3), at a plant height of 18.96 cm, stem diameter of 1.169, fruit weight of 630 grams, fruit length 43.50 cm and fruit diameter 75.66 cm.